Fostering Spatial Comprehension in Solid Geometry: The Role of Augmented Reality and GeoGebra - Sekulić, Tanja; Nikolić, Sanja; Hilčenko, Slavoljub (Rzeszów University Press, 2025)
Augmented reality (AR) represents an innovative digital technology capable of fostering a learning environment that enhances the understanding of spatial concepts, mathematical objects, and the relationships between them. This paper looks into the features of AR and its practical applications in mathematics, highlighting its transformative potential in classrooms. Addressing challenges in solid geometry, such as the visualization and representation of three-dimensional (3D) spaces, AR emerges as a powerful tool, offering a dynamic means to explore and interact with geometric objects within real-world contexts. A particular focus is placed on the GeoGebra 3D Calculator and its integrated AR module. Through four carefully selected examples from solid geometry, we provide detailed demonstrations of how these tools can be used to solve complex problems, thereby bridging the gap between theoretical concepts and practical understanding. These examples illustrate the profound impact of AR technology on improving spatial comprehension and engaging learners in mathematics.
Keywords: Augmented reality; GeoGebra; 3D Calculator; Solid geometry; Spatial visualization